Formulation And Evaluation Of Terminalia Arjuna-Based Oral Suspension For Anti-Inflammatory Activity - Verma, Ayush; Kumar Vyas, Girish; Nama, Nitin (Journal of Neonatal Surgery, 2025)
The study focuses on the development and evaluation of an oral suspension containing Terminalia arjuna extract, a plant renowned for its anti-inflammatory, cardioprotective, and antioxidant properties. The formulation aimed to provide a stable, effective, and easily administered dosage form for potential cardiovascular health support. The extract was prepared from the bark of T. arjuna using ethanol, and the suspension was formulated with excipients like xanthan gum, sucrose, and preservatives. The final product was evaluated for physicochemical properties, stability, microbial safety, and in vitro drug release. Results indicated that the optimal formulation (F2) showed excellent stability, uniform drug content, and sustained release, with 80.5% drug release after 120 minutes. The formulation met all evaluation criteria, demonstrating its potential as a safe and effective therapeutic option for inflammation and cardiovascular conditions.